Self-Medication and Contributing Factors Among Pregnant Women Attending Antenatal Care at Public Hospitals of Harar Town, Ethiopia - Jambo, Abera; Mengistu, Getnet; Sisay, Mekonnen; Amare, Firehiwot; Edessa, Dumessa (Frontiers in Pharmacology, 2018)
Background: Self-medication has been increasing in many developing and developed countries. Its use during pregnancy presents a major challenge due to potential undesirable effects on mother and the fetus. So the aim of this study was to assess the prevalence of self-medication and contributing factors, among pregnant women. Methodology: Institution based cross sectional study was conducted among 244 pregnant women attending antenatal care at Hiwot Fana Specialized University Hospital and Jugal Hospital from February to March, 2017. A structured questionnaire based interview was used to collect data from each study subject. Then, data were categorized and analyzed using SPSS version 20 software. Logistic regression analysis was used to determine the significance of the association between the outcome and independent variables. P-value < 0.05 was considered as a statistically significant in multivariate analysis. Results: The prevalence of self-medication during current pregnancy was 69.4%; out of which, 40.6% uses only herbal medicines to self medicate. Time saving (50.7%) and prior experience of the drug (25.35%) were the main reasons for self-medication using conventional medicines while fewer side effects (59.86%) and effectiveness (35.92%) were the common reasons for self medication using herbal medicines. Common cold and headache were among the common indications for self-medication. Friends (28.17%) and the pharmacist/ druggist (23.94%) were the commonest source of information for conventional medicines while family/friends (69.72%) and neighbors (26.76%) were the common source of information for herbal medicines. Community drug retail outlets and neighbors were the commonly used sources of conventional medicines; while market place and self-preparation were the common sources of herbal medicines. Previous history of self-medication was significantly associated (P<0.05) with current self-medication with conventional drugs and being a farmer by occupation and poor monthly income were significantly associated with herbal medicine use during pregnancy (p<0.05). Conclusion: The prevalence of self-medication during pregnancy was very high in this study which showed a need for public trainnings for all women of reproductive age about the risks of inappropriate self-medication.